2020
DOI: 10.4102/jomped.v4i1.97
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anxiolytic potential and acute toxicity study of Combretum micranthum G. Don. leaves (Combretaceae)

Abstract: Background: Combretum micranthum G. Don. (Combretaceae) is an ethnomedicinally valuable, undomesticated and indigenous shrub of West Africa. However, its anxiolytic potential have not been reported despite its ethanolic extract being used ethnomedicinally in the management of anxiety disorders.Aim: To determine the acute toxicity effect and assess the behavioural effects and anxiolytic potential of C. micranthum G. Don. leaves in mice.Settings: This study is an experimental design to evaluate the ethnomedicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Toxicity Amali et al (2020) showed that C. micranthum has no toxicity when administered orally to mice (LD 50 � 2000 mg/kg). [74] This result was confirmed by the Mogue team (2020) which reported the same LD 50 . [79] On the other hand, Kpemissi et al (2020) evaluated the potential toxicity of the hydroalcoholic leaf extract, through the acute and subchronic oral administration method in rats.…”
Section: Other Activitiesmentioning
confidence: 59%
See 4 more Smart Citations
“…Toxicity Amali et al (2020) showed that C. micranthum has no toxicity when administered orally to mice (LD 50 � 2000 mg/kg). [74] This result was confirmed by the Mogue team (2020) which reported the same LD 50 . [79] On the other hand, Kpemissi et al (2020) evaluated the potential toxicity of the hydroalcoholic leaf extract, through the acute and subchronic oral administration method in rats.…”
Section: Other Activitiesmentioning
confidence: 59%
“…Amali et al . (2020) showed that C. micranthum has no toxicity when administered orally to mice (LD 50 ≥2000 mg/kg) [74] . This result was confirmed by the Mogue team (2020) which reported the same LD 50 [79]…”
Section: Toxicitymentioning
confidence: 81%
See 3 more Smart Citations